Impact of small-scale irrigation schemes on household income and the likelihood of poverty in the Lake Tana basin of Ethiopia - Ayele, Getaneh K.; Nicholson, C.; Collick, A.S.; Tilahun, Seifu A.; Steenhuis, Tammo S. (International Livestock Research Institute, 2013)
This study uses Tobit and Logit models to examine the impacts of selected small-scale irrigation schemes in the Lake Tana basin of Ethiopia on household income and the likelihood of poverty, respectively. Data for these analyses were collected from a sample of 180 households. Households using any of the four irrigation systems had statistically significantly higher mean total gross household income than households not using irrigation. The marginal impact of small-scale irrigation on gross household income indicated that each small scale-irrigation user increased mean annual household income by ETB 3353 per year, a 27% increase over income for non-irrigating households. A Logit regression model indicated that access to irrigation significantly reduced the odds that a household would be in the lowest quartile of household income, the poverty threshold used in this study. Households using concrete canal river diversion had higher mean cropping income per household than those using other irrigation types. Key challenges to further enhancing the benefits of irrigation in the region include water seepage, equity of water distribution, availability of irrigation equipment, marketing of irrigated crops and crop diseases facilitated by irrigation practices.